Actual Experience of One and a Half Ventricle Repair in Patients with Ebstein’s Anomaly - KhanenovaV. А.; Stogova, O. V.; Hrytsaiuk, A. Y.; Kuzmenko, Y. L.; Meshkova, M. S.; Yalynska, T. A.; Kostrakevych, R. M.; YemetsІ. М. (Ukrainian Journal of Cardiovascular Surgery, 2019)
Introduction. Ebstein’s anomaly (EA) is a complex congenital heart defect involving mainly tricuspid valve (TV), right atrium and right ventricle (RV). Severe RV systolic dysfunction is associated with a high risk of surgical intervention for EA. Bidirectional cavopulmonary shunt (BCPS), which complements the restoration of TV competence, is an important step in one and a half ventricle repair. The aim. To analyze actual experience of EA treatment through the method of one and a half ventricle repair. Materials and methods. In the period from 1999 to 2018, one and a half ventricle repair of EA was performed in 17 patients at the UCCC. Preoperative examinations showed type “B” EA in 4 (23.5 %) patients, type “C” in 8 (47 %), type “D” in 5 (29.5 %) patients. BCPS was combined with different types of TV plasty in 14 (82.4 %) patients, with TV replacement in 3 (17.6 %) patients. Results and discussion. Early postoperative mortality rate was 5.9 %; 1 (6.2 %) reoperation was performed. In the early postoperative period, the contractility of both ventricles was satisfactory, TV insufficiency was from mild to moderate. The average duration of the late postoperative period was 102.6 ± 58.8 months. Most patients maintained small to moderate TV insufficiency, and contractility of both ventricles was satisfactory. The long-term mortality rate was 12.5 %. Also, 3 (18.7 %) reoperations were performed. Conclusions. One and a half ventricular repair of EA may be used for surgical treatment of patients with EA and RV severe dilatation and systolic dysfunction, acute decrease in cardiac output due to the changes in LV geometry and contraction as well as non-ideal correction of TV insufficiency.